O apoio institucional como uma das faces da função apoio no Núcleo de Apoio à Saúde da Família (NASF): para além das diretrizes - Moura, Renata Heller De; Luzio, Cristina Amélia (UNESP, 2014)
The aim of this study was to add to the debate about Family Health Support Centers (FHSCs), starting from reflections about the support function. Support is generally presented, in official documents from the Ministry of Health and in academic-scientific publications, accompanied by descriptors that characterize it. Differences in terminology are commonly encountered: “institutional support”, “managerial support”, “matrix support” and so on. With regard to FHSCs, published papers have highlighted the central role played by matrix support. However, we pose the question: what are the faces that the support function has been taking on in implementing such programs? To reflect on this and other issues, we developed a study of qualitative nature within a FHSC team in Paraná, outside of the state capital, using the methodological tools of participant observation, semi-structured interviews and discussion groups. We sought to demonstrate that the dynamics of the support function in FHSCs make it possible for both matrix support and institutional support to emerge.

El objetivo de este trabajo es aumentar el debate sobre el NASF, a partir de una reflexión sobre la función de apoyo. Por lo general, tal función se presenta en los documentos del Ministerio de Salud y en las publicaciones académicas y científicas, acompañada de descripciones que la caracterizan. Solemos encontrar diferentes tecnologías, como: “apoyo institucional”, “apoyo a la gestión”, “apoyo matricial”. En relación al NASF, las publicaciones examinadas destacan la característica central del desempeño del apoyo matricial. Sin embargo, nos preguntamos: ¿cuáles son los aspectos que la función de apoyo ha tenido en la implementación de este programa? Para reflexionar sobre esa y otras cuestiones, hemos desarrollado un estudio de carácter cualitativo en un equipo del NASF, en el interior del Estado de Paraná, utilizando las herramientas metodológicas: observación participativa, entrevistas semi-estructuradas y grupos de discusión. Buscamos demostrar que la dinámica de la función de apoyo en el NASF permite el surgimiento tanto del apoyo matricial como del institucional.

O propósito deste trabalho é incrementar o debate sobre o NASF, a partir de uma reflexão acerca da função apoio. A palavra apoio é, geralmente, apresentada, em documentos oficiais do Ministério da Saúde e em publicações acadêmico-científicas, acompanhada por descritores que a caracterizam. É comum encontrarmos diferentes terminologias: “apoio institucional”, “apoio à gestão”, “apoio matricial”. Quanto ao NASF, publicações examinadas destacam a centralidade do desempenho do apoio matricial. No entanto, nos perguntamos: quais as faces que a função apoio vem assumindo na implementação deste programa? Para refletir sobre essa e outras questões, desenvolvemos uma pesquisa de caráter qualitativo em uma equipe de NASF, no interior do Paraná, utilizando-nos das ferramentas metodológicas: observação participante, entrevista semiestruturada e grupos de discussão. Procuramos demonstrar que a dinâmica da função apoio no NASF permite a emergência tanto do apoio matricial quanto do apoio institucional.
Institutional support as one of the faces of the support function in Family Health Support Centers (FHSCs): going beyond the guidelines
El apoyo institucional como uno de los aspectos de la función de apoyo en el Núcleo de Apoyo a la Salud de la Familia (NASF)
Keywords: Institutional Support; Matrix support; Family Health Support Center; Primary Care; Public Health; Apoio institucional; Apoio matricial; Núcleo de Apoio à Saúde da Família; Atenção Primária à Saúde; Saúde Pública